UJI ANTIOKSIDAN EKSTRAK AIR DAN EKSTRAK ETANOL DAGING DAN KULIT BUAH BLEWAH (Cucumis melo L.) - Antonius Padua Ratu; Herson Cahaya Himawan; M. Rio Radhi (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
High content of sitrulin can contribute to oxidative stress as a free radical scavenger. Plants from the Cucurbitaceae family are found in high quantities of Citrulline. One of Cucurbitaceae family is cantaloupe (Cucumis melo L.) The purpose of this study was to determine the antioxidant activity which is optimal in the flesh and rind cantaloupe against extraction methods. The method was used maceration with the ethanol and water, methods of digestion and decocta only with water solvent. The high antioxidant activity was shown by ethanol extract cantaloupe was rind maceration method (583.19 mg/L). In the water extract, rind maceration method of cantaloupe provides antioxidant activity (722.17 mg/L) were significantly different (P<0,05) than the water solvent digestion method and decocta method. However, the antioxidant activity of the flesh and rind extract from cantaloupe is lower than vitamin C.